TILRR, a novel IL-1RI co-receptor, potentiates MyD88 recruitment to control ras-dependent amplification of NF-?B - O'NEILL, LUKE ANTHONY JOHN (The American Society for Biochemistry and Molecular Biology, 2010)
Host defense against infection is induced by Toll-like and interleukin (IL)-1 receptors, and controlled by the transcription factor NF-?B. Our earlier studies have shown that IL-1 activation impacts cytoskeletal structure and that IL-1 receptor (IL-1RI) function is substrate-dependent. Here we identify a novel regulatory component, TILRR, which amplifies activation of IL-1RI and coordinates IL-1-induced control with mechanotransduction. We show that TILRR is a highly conserved and widely expressed enhancer of IL-1-regulated inflammatory responses and, further, that it is a membrane-bound glycosylated protein with sequence homology to members of the FRAS-1 family. We demonstrate that TILRR is recruited to the IL-1 receptor complex and magnifies signal amplification by increasing receptor expression and ligand binding. In addition, we show that the consequent potentiation of NF-?B is controlled through IL-1RI-associated signaling components in coordination with activation of the Ras GTPase. Using mutagenesis, we demonstrate that TILRR function is dependent on association with its signaling partner and, further, that formation of the TILRR-containing IL-1RI complex imparts enhanced association of the MyD88 adapter during ligand-induced activation of NF-?B. We conclude that TILRR is an IL-1RI co-receptor, which associates with the signaling receptor complex to enhance recruitment of MyD88 and control Ras-dependent amplification of NF-?B and inflammatory responses.
PUBLISHED
Keywords: Immunology; Interleukin-1 Receptor Type 1